Judaism - Wood, Angela Gluck (Laguna Hills, CA QEB Publishing, Inc., 2006)
Explore the fsacinating world of Judaism and find out how one of the oldest religions in the world began. Discover its art and learn about Jewish beliefs, traditions, and colorful festivals.
5 - 9
Keywords: Jews; Religions; World of Faiths